THE IMPLEMENTATION OF SCAFFOLDING READING EXPERIENCE STRATEGY IN INCREASING STUDENTS’ COMPREHENSION - Cut Herawati; Sofyan A. Gani; Asnawi Muslim (JETLi: Journal of English Teaching and Linguistics, 2020)
The aim of this research is to find out whether there is a significant difference in achievement between students who were thought reading comprehension by using SRE strategy and those who are not, and to examine the students’ responses toward the SRE strategy used in teaching reading comprehension. The method used in this study was experimental design in which classified into experimental and control groups. The population of the study was the first-grade students of State Vocational School 1 Nisam, North Aceh. The data were collected through a reading comprehension test and a set of questionnaires. The finding showed significant differences between the pre-test and post-test score. The result showed that the means of pre-test for both class of experimental was M=46, 79, SD = 14, 15) to post test (M = 75, 36, SD = 12, 01), t (27) = -11, 92, p < .001 (two-tailed). The data squared statistics (.84) indicated a large effect size. The mean increase from the test illustrated significant difference between pre-test and post-test, hence the hypothesis was accepted. Furthermore, the result of data analysis from the questionnaire showed that most of the students responded positively.